CONDEMNED POLITICIANS: THE DESIRES AND DEFENSES THAT PERMEATE THEIR SPEECH - Souza, Elizandra (Revista Gênero e Interdisciplinaridade, 2023)
The article makes an interlocution between Psychoanalysis, Discourse Analysis and Criminology, using the ADL (David Libermerman Algorithm) as a theoretical instrument. It covers the understanding of theoretical concepts and the possibility of application in the analysis of the testimony of politicians who were convicted of white collar crimes. In this work we propose the presentation of the objectives, the research problem and the theoretical framework.